Visibility and accessibility of information science dissertations in Spain - Rodríguez-Yunta, Luis (Anuario ThinkEPI, 2010)
This contribution examines the visibility and accessibility of the doctoral dissertations in Library and Information Science in Spanish universities. The analysis shows the inadequacies of available resources that locate the theses in this discipline and calculate the percentage available as full text. Finally, a reflection about the use of classifications in the document databases is included.
Keywords: Thesis; Dissertations; Visibility; Availability; Accesibility; Library science; Information science; Spain.